2019
DOI: 10.31396/biodiv.jour.2019.10.2.127.140
|View full text |Cite
|
Sign up to set email alerts
|

Diatoms diversity and dynamics in a southern Mediterranean lagoon (Mellah, Algeria)

Abstract: The composition and distribution of diatoms were studied using a biweekly sampling performed in three representative stations in the Mellah Lagoon (South Western Mediterranean, Algeria), during 2016. In total, 160 diatoms species-belonging to centric species (52 species) and pennate species (108 species)-were inventoried. The relative abundance of the pennate forms (67.50%) is clearly higher compared to the centric forms (32.50%). The blooms of diatoms are represented by 3 species: Chaetoceros constrictus Gran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Similarly, the authors have shown the dominance of genus Diatoma with a rate of 42.37% as compared with the genus Nitzschia (17.5%) found at the Rhiou river, since the genera Nitzschia et Navicula are predominant in Malah river, along with rates of 63.87% and 18.5% respectively. However, the study of Draredja et al (2019a), in the Melleh lagoon, indicates that the dominant genus is Nitzschia. The study of Chabaca et al (2020), in the Oubeira lake, indicated that the genera Cyclotella and Nitzschia dominated the lake.…”
Section: Composition Of Diatom Communitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the authors have shown the dominance of genus Diatoma with a rate of 42.37% as compared with the genus Nitzschia (17.5%) found at the Rhiou river, since the genera Nitzschia et Navicula are predominant in Malah river, along with rates of 63.87% and 18.5% respectively. However, the study of Draredja et al (2019a), in the Melleh lagoon, indicates that the dominant genus is Nitzschia. The study of Chabaca et al (2020), in the Oubeira lake, indicated that the genera Cyclotella and Nitzschia dominated the lake.…”
Section: Composition Of Diatom Communitiesmentioning
confidence: 99%
“…However, the study performed by Nehar (2016) has revealed that the results of settlement structure from El-Hammam and Chelif rivers (North-est Algeria) provided generally, low mean values. On the other hand, Draredja et al (2019a) reported that the diversity of populations of diatoms in the Mellah is up to 4.56 bits.cell -1 and with a of regularity of 0.98, and thus suggesting populations of structured diatoms for a single period of the year (winter and late spring). However, the rest of the cycle is characterized by unstable species composition.…”
Section: Composition Of Diatom Communitiesmentioning
confidence: 99%
“…8.6 km 2 . With an mean depth of 3.5 m (Messerer, 1999;Draredja, 2007), EML connects to the sea via a channel ca. 870 m long, 20 m wide, and 0.5-2.0 m deep (Draredja, 2007).…”
Section: Study Areamentioning
confidence: 99%
“…With an mean depth of 3.5 m (Messerer, 1999;Draredja, 2007), EML connects to the sea via a channel ca. 870 m long, 20 m wide, and 0.5-2.0 m deep (Draredja, 2007). It receives freshwater from three intermittent rivers (wadis): El-Mellah and Bélaroug in the south and R'Kibet in the north-west.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation